Higher Order Expectations in Asset Pricing - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 2004)
In this paper, we examine formally Keynes' idea that higher order beliefs can drive a wedge between an asset price and its fundamental value based on expected future payoffs. In a dynamic noisy rational expectations model, higher order expectations add an additional term, which we call the higher order wedge, to a standard asset pricing equation. Consistent with Keynes' reasoning we show that investment decisions are based not just on expected future payoffs, but also on anticipated future expectational errors made by the market. The latter are captured by the higher order wedge. We show that the expectation of future expectational errors by the market is perfectly rational when investors have both noisy public and private information. The main effect of this additional asset pricing term is to disconnect the price from the present value of future payoffs. We show that this effect can be quantitatively significant.
Keywords: 330; CAPM; Zinsstruktur; Keynesianismus; Erwartungsbildung; Theorie